Inside Computer Music - Clarke, Michael 1956-; Dufeu, Frédéric; Manning, Peter, 1948- (New York Oxford University Press, 2020)
"This publication (the text and the software) aims to explore the relationship between new technical innovations in computer technology for music and the creative practice of composers employing these new techniques. It asks: does the new technology lead to new sounds and new ways of structuring music, and if so how? What are the creative options, sonic and structural, presented by new software and hardware? How can these be manipulated and shaped to form music? How have particular composers developed successful working methods in using this technology? To answer such questions a set of case studies have been examined in depth, specific works in which composers have adopted new techniques, whether developed by themselves or by others. Each of these works has been researched from a number of different perspectives: the technical and musical background, the technology employed in the particular work and, through music analysis, the musical outcome. Innovative approaches have been employed both in undertaking and presenting this research. On the one hand, it has been important to find appropriate ways of presenting the musical potential of what are often highly technical processes. On the other hand, it has been necessary to find ways of analyzing music that often evades even the most basic fundamentals of traditional music analysis: notes, harmonies, or instruments"--
Nine case studies from the history of computer music: John Chowning - Stria ; Barry Truax - Riverrun ; Philippe Manoury - Pluton ; Hildegard Westerkamp - Beneath the Forest Floor ; Francis Dhomont - Phonurgie ; Trevor Wishart - Imago ; Jonathan Harvey - Fourth String Quartet ; Cort Lippe - Music for Tuba and Computer ; Natasha Barrett - Hidden Values - The Lock -- Conclusions.
Includes bibliographical references (pages 393-403) and index.
Keywords: Computer science; Musical analysis; Music criticism; Music philosophy and esthetics; Technology